RENCANA STRATEGI PENGEMBANGAN PROGRAM STUDI (STUDI KASUS: PRODI D3 MP-WNBK PNJ) - Innas Rovino Katuruni (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2021)
The world of education is still growing and is one of the main pillars of support for human life, including Education for Citizens with Special Needs. One of the institutions that organizes education for Citizens with Special Needs is the MP-WNBK PNJ Diplome-3 Study Program. The making of this strategic plan is in order to provide input and views for the academic community of the Study Program regarding the current internal and external conditions of the study program. This plan is made using a strategic management approach at the institutional scale. This research was conducted at the MP-WNBK Diplome-3 Study Program PNJ during May to October 2021. Internal respondents in this study were the Head of the Study Program, Teaching Staff, Administrative Staff, and Study Program Students. External respondents in this study were the Alumni of the Study Program. The data used in this study are primary data and secondary data. Primary data in the form of direct observation data in the form of interviews conducted by Focus Group Discussion (FGD) with each respondent. From the results of the study, it was concluded that the results of the IE matrix analysis showed that the MP-WNBK Study Program occupies cell II. This Growth position is in accordance with the condition of the MP-WNBK Study Program which can still continue to grow and develop. The strategy needed according to the IE matrix is in accordance with what the MP-WNBK Study Program should do now, namely penetration and developing the study program internally and externally